PERALIHAN HAK GUNA BANGUNAN MENJADI HAK MILIK BERDASARKAN PERATURAN PEMERINTAH NO. 18 TAHUN 2021 TENTANG HAK PENGELOLAAN, HAK ATAS TANAH, SATUAN RUMAH SUSUN, DAN PENDAFTARAN TANAH - Elsura, Aqliyah Hafifah; Lubis, Syaddan Dintara (Universitas Islam Kadiri, 2024)
In Indonesia, the need for land is increasing day by day due to a significant increase in population. This causes the value of the land to increase. The increasing value of land can result in every community always cultivating the land. Forms of land cultivation can be done in various ways such as ways that are in accordance with the law and ways that are against the law. As an effort to protect land rights owners, land certificates are issued. According to Government Regulation Number 24 of 1997 concerning Land Registration in Article 32 paragraph (1) what is meant by a certificate is,